Comparison of Physicochemical Properties, Volatile Profiles, and 5-Hydroxymethylfurfural and Acrylamide Content in Whole and Explosion-Puffed Wheat Grain - Nurzat Konkubaeva; Vitalijs Radenkovs; Lolita Tomsone; Anete Keke; Asylbek Kulmyrzaev; Ruta Galoburda (Applied Sciences)
The study aimed to investigate the effects of pre-treatment (husking, sifting, and moisture adjustment) and explosion puffing on the chemical composition, volatile profile, phenolic content (free and bound), radical-scavenging activity, and formation of potentially hazardous compounds in wheat grain. Processing decreased protein, fat, ash, and dietary fiber content primarily due to removing the aleurone layer and thermal degradation leading to a diminished overall nutritional value. However, the starch content increased, along with significant changes in mono- and disaccharides, including higher maltose and glucose content attributed to starch gelatinization and hydrolysis. Thermal processing significantly altered the volatile profile, introducing new aroma-active compounds, such as pyrazines and furans, formed through Maillard and caramelization reactions. Additionally, the content of spectrophotometrically determined free phenolics and flavonoids increased, enhancing the grains’ radical-scavenging potential. Safety analyses confirmed that 5-hydroxymethylfurfural (5-HMF) and acrylamide levels remained within permissible limits, ensuring compliance with food safety standards. These findings highlight the nutritional and safety implications of explosion puffing, emphasizing its potential as a wheat-processing method.